60-month follow-up of Long Limb vs. Standard Limb Roux-en-Y gastric bypass for type 2 diabetes and obesity: the LONG LIMB RCT - Saleem Ansari; Anna Kamocka; Tina Mazaheri; Ibiyemi Ilesanmi; Lara Jimenez-Pacheco; Kleopatra Alexiadou; Joanna Tan; Harvinder Chahal; Krishna Moorthy; Sanjay Purkayastha; Anne Margot Umpleby; Stephen Robert Bloom; et al. (Efficacy and Mechanism Evaluation)
Background Roux-en-Y gastric bypass is an established treatment option for type 2 diabetes and obesity. However, the optimal lengths for the small intestinal limbs remain controversial with variation in practice. A longer biliopancreatic limb length of 150 cm (‘Long Limb’) was hypothesised to better improve glycaemia compared to the standard Roux-en-Y gastric bypass with a biliopancreatic limb of 50 cm (‘Standard Limb’). The aim of the trial was to evaluate the short-term mechanistic outcomes and the long-term clinical outcomes and safety of Long Limb versus Standard Limb Roux-en-Y gastric bypass. Methods We undertook a prospective double-blinded randomised controlled parallel group clinical trial across two sites in London. Participants were randomly assigned (1 : 1) to Long Limb or Standard Limb Roux-en-Y gastric bypass with a fixed alimentary limb of 100 cm. Mixed-meal tolerance tests and a hyperinsulinaemic-euglycaemic clamp were used to measure postprandial gut hormone response, glucose tolerance and insulin sensitivity. The primary outcome for the mechanistic study was the secretion of active glucagon-like peptide-1 at 2 weeks after intervention. Secondary outcomes were insulin sensitivity and fasting/postprandial glucose and insulin concentrations. Clinical outcomes, including HbA1c, number of glucose-lowering medications, weight loss, blood pressure and low-density lipoprotein cholesterol, and adverse events, were collected up to 60 months postoperatively to assess the durability of postoperative weight and glycaemic improvements. Results Of the 53 participants randomised, 48 completed the 12-month mechanistic investigation (Standard Limb 24, Long Limb 24) and 38 completed the 60-month follow-up (Standard Limb 18, Long Limb 20). The 24- to 60-month extension study coincided with two waves of the COVID-19 pandemic. There was no difference between the Standard Limb and Long Limb groups for postprandial active glucagon-like peptide-1 secretion (70 ± 32 pmol/L vs. 70 ± 19 pmol/L, respectively; p = 0.43), hepatic insulin sensitivity (3.4 ± 0.9 µmol/kg/min vs. 3.4 ± 1.4 µmol/kg/min, respectively; p = 0.94) and peripheral insulin sensitivity (29.0 ± 9.1 µmol/kg/min vs. 29.2 ± 9.9 µmol/kg/min, respectively; p = 0.98) at 2 weeks post intervention. There was no difference between the Standard Limb and Long Limb groups at 60-month follow-up for glycaemic remission (33% vs. 45%, respectively; p = 0.52), percentage total weight loss (27 ± 9% vs. 26 ± 8%, respectively; p = 0.34), systolic blood pressure (127 ± 11 mmHg vs. 125 ± 14 mmHg, respectively; p = 0.63) and low-density lipoprotein cholesterol (2.0 ± 1.0 mmol/L vs. 2.4 ± 1.0 mmol/L, respectively; p = 0.27). Conclusion In conclusion, this study has demonstrated the substantial clinical benefit of Roux-en-Y gastric bypass to people living with type 2 diabetes and obesity; however, this trial did not demonstrate a clinical rationale for the elongation of the biliopancreatic limb of Roux-en-Y gastric bypass to 150 cm to enhance metabolic outcomes for type 2 diabetes and obesity. Limitations Although the surgical procedures were designed according to United Kingdom clinical practice at the time of study inception, there is substantial variation in practice internationally. Our original investigation was powered for mechanistic outcomes and is not powered to detect differences in clinical outcomes. Lastly, the loss of participants to follow-up may have limited our statistical power to detect significant differences in the clinical outcomes. We therefore cannot derive definitive conclusions on the relative clinical efficacy of the two variants of Roux-en-Y gastric bypass. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Efficacy and Mechanism Evaluation (EME) programme as award number NIHR130639. Plain language summary Weight loss surgery, such as gastric bypass, is routinely used to treat people with type 2 diabetes and obesity worldwide. This is because the surgery is effective at lowering weight and improving blood sugar. In some people with diabetes this means that they can come off medications and still have normal blood sugar: this is called diabetes remission. However, the standard gastric bypass surgery only results in diabetes remission in 4 out of 10 patients, and it would be better if we could improve this success rate. In this trial a new surgery called ‘Long Limb’ gastric bypass was tested. It was designed to be better at improving diabetes mellitus than the older ‘Standard Limb’ gastric bypass surgery, while being just as safe. It was expected that this new procedure would work better than the Standard Limb gastric bypass by increasing the release of insulin and other hormones from the gut and by improving weight loss and blood sugar over and above the standard operation. We found that the Standard and Long Limb operations were equally effective in reducing blood sugar and reducing weight. When followed up to 60 months (5 years) after the surgery, people who had either Standard or Long Limb had similar experiences, with lasting weight loss and improvement in blood sugar levels, but there was no significant difference between the older and the newer type of surgery. Our study shows that there does not appear to be a large difference between the two types of surgery: both seem to be similarly effective at helping people to lose weight and improve their diabetes.